(untitled) (International Journal of Academic Research in Progressive Education and Development, 2022)
During the Covid19 pandemic, universities around the world had to transformed from the classroom learning into an online learning environment. Varieties of learning Management System (LMS) were developed by respective universities and software companies to assist the learning process. In Universiti Teknologi MARA (UiTM), UFuture platform is developed to assist in the teaching and learning process. However, there is little information on the user experience (UX) among the students interacting with UFuture. This paper attempt to address the user experience of UFuture usage. The data were gathered from a focus group study consists of 50 postgraduate students that has experiences using UFuture platform for learning. The study used a standard User Experiences Questionnaire (UEQ) comprised of 26 questions in measuring six (6) scales which are Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty. The descriptive analysis result indicates neutral evaluation, where the mean values of each scale within -0.8 to 0.8. In addition, the benchmarking between UiTM UFuture against UEQ dataset shows that the learning platform scored “below average”. For future work it is suggested, element of attractiveness, efficiency, stimulation and dependability of UFuture platform should be enhanced to heighten the overall student’s user experience (UX).